Maksimalkan Penginjilan Anak Muda: Efektivitas Media Sosial Dengan Aplikasi Litmatch - Fernando Laduri , Jack; Sunkudon, Pieter G.O. (Sekolah Tinggi Teologi Injili Indonesia Palu, 2024)
This study evaluates the effectiveness of the Litmatch app as an evangelism tool for young Christians. In the digital age, social media has become an important platform for spreading religious messages. The focus of the study was the use of Litmatch, which is popular among young people, to communicate the gospel and increase participation in evangelism. Descriptive quantitative research methods were used with data from observations, interviews, and questionnaires with 45 young Christians who are active users of Litmatch in Palu City. Data analysis using the SPSS program evaluated the effectiveness of the app in providing a space for questions, teaching correct evangelism, and providing appropriate gospel information. The results showed that Litmatch is effective as an evangelistic medium, with key indicators including clarity of purpose, strategies for success, and appropriate programs. The use of social media such as Litmatch can overcome the challenges of traditional evangelism by reaching a wider audience without geographical limitations. This research provides important insights into the role of social media in evangelism and church ministry, and offers practical recommendations for maximizing Litmatch in evangelistic missions in the digital age.